Inequitable Administration: Documenting Family for Tax Purposes - Infanti, Anthony C. (Columbia Journal of Gender and Law, 2011)
Family can bring us joy, and it can bring us grief. It can also bring us tax benefits and tax detriments. Often, as a means of ensuring compliance with Internal Revenue Code provisions that turn on a family relationship, taxpayers are required to document their relationship with a family member. Most visibly, taxpayers are denied an additional personal exemption for a child or other dependent unless they furnish the individual’s name, Social Security number, and relationship to the taxpayer. In this article, I undertake the first systematic examination of these documentation requirements. Given the privileging of the “traditional” family throughout the Code, one might expect to see that same privileging mirrored in the administrative structure that underpins the Code’s family tax provisions. Indeed, on their very face, the information-reporting rules that apply to jointly owned income-producing property do just that. Once the inquiry is expanded to cover other family tax provisions, however, it quickly becomes clear that the administrative structure underpinning the family tax provisions has also been strongly influenced by endemic privilegings along a variety of other axes of subordination—from class to race to gender to sexual orientation. To address and remedy these defects in the administrative structure underpinning the family tax provisions, this article advocates an approach to documenting family for tax purposes that does not invidiously discriminate among taxpayers.